Gated prey [compact disc, unabridged] - Goldberg, Lee, 1962- (Goldberg, Lee, 1962- Eve Ronin series., 2021)
While on a sting operation in a gated, luxury enclave in Calabasas, detective Eve Ronin and her soon-to-retire partner, Duncan Pavone, successfully catch home invaders but have unanswered questions.